Impact of Superluminal Speeds and Dimensional Complexities on Space-Time - Abiri, Abdul-Hafiz G.; Oni-Ojo, Amenaghawon A.; Ejere, Arthur I.I. (NIU Journal of Climate Justice and Governance, 2026)
In this work, the effect of superluminal speeds and higher dimensions on space-time was examined. Einstein’s theories of special and general relativity were fundamental to this study. The theoretical research method was thus used, with special interest in the Lorentz factor, so as to derive the level of uncertainties of superluminal speeds; based on geometry, inertia and causality. Two null-hypothesis were formulated: the first to determine the level of uncertainty beyond the light-cone (the causal boundary), and the second to examine the relationship between the generalized Lorentz factor and extra-dimensional contributions. Apart from Einstein’s theories of Special and General Relativity, other foundational theories relevant to this work are the Kaluza/Klein extra dimensions, string theory and Minkowski space-time. In testing hypothesis one, theoretical methods were used to derive what we call the Superluminal Triple Uncertainty Principle (STUP), which operates similarly to the Heisenberg Uncertainty Principle. The STUP hinges on an already established fact that under superluminal motion, at least one of geometry, inertia and causality will collapse. Finally, we tested hypothesis two by introducing the extra-dimensional complexity factor. We observed that this factor induces a hidden velocity component, such that the system behaves relativistically, though the ordinary velocity is fixed. Keywords: Superluminal; Relativistic; Inertia; Causality; Uncertainty Principle; Triple Uncertainty Bound.